2023
DOI: 10.1111/epi.17523
|View full text |Cite
|
Sign up to set email alerts
|

The etiology and mortality of new‐onset refractory status epilepticus (NORSE) in adults: A systematic review and meta‐analysis

Abstract: New-onset refractory status epilepticus (NORSE) is a devastating neurological presentation. There is a paucity of large studies on NORSE as it is a relatively new clinical syndrome. The aim of this review was to summarize the etiologies and establish a mortality rate for NORSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
(195 reference statements)
0
9
0
Order By: Relevance
“…Likely, there are yet autoantibodies to discover or they have been discovered at the time point of diagnosis, which might account for some but not all of the cryptogenic cases. 5 In a mixed cohort comprising adults and children, Gopaul et al 7 linked the seasonal differences with AEs that have a higher reported prevalence in summer-autumn and in warmer months. 18,19 However, data from a Danish AE register did not suggest a strong seasonality of antibody detection in Denmark making a direct and substantial link between the seasonality of NORSE and AE less likely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likely, there are yet autoantibodies to discover or they have been discovered at the time point of diagnosis, which might account for some but not all of the cryptogenic cases. 5 In a mixed cohort comprising adults and children, Gopaul et al 7 linked the seasonal differences with AEs that have a higher reported prevalence in summer-autumn and in warmer months. 18,19 However, data from a Danish AE register did not suggest a strong seasonality of antibody detection in Denmark making a direct and substantial link between the seasonality of NORSE and AE less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Around one third of NORSE patients have autoimmune encephalitis (AE), the remainder is caused by infections (e.g., herpes encephalitis) and various rare etiologies. 5,6 Seasonal variations may provide important hints towards the precipitating triggers of NORSE and may therefore help with understanding the pathophysiological mechanisms causing cryptogenic NORSE. Gopaul et al recently examined the seasonality of adult and pediatric NORSE patients from four different cohorts from North America, Germany, and Belgium.…”
Section: Plain Language Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…NORSE/FIRES represent a devastating condition with high mortality rates and poor neurocognitive outcomes ( 58 ). The necessity of rapid effective treatment is reflected in the timeline of the current therapeutic consensus ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…It will therefore be necessary to look for other signs of encephalitis, such as recent psychiatric or cognitive symptoms, abnormal movements (clonus, myoclonus, dyskinesia, dystonia), MRI-hyperintensities (especially in temporal regions), lymphocytic meningitis on lumbar puncture and EEG abnormalities [15–17]. A systematic review of the etiologies of NORSE highlighted that an autoimmune etiology was identified in 36.2%, whilst no cause was identified in almost half of cases (49.9%) [18 ▪ ]. Regarding causes of SRSE, a recent study highlighted that the only independent predictor of this severe form of SE was central nervous system infection [4], suggesting that the neuro-inflammatory process in infectious encephalitis could induce major neuronal excitotoxicity [16].…”
Section: Aetiologiesmentioning
confidence: 99%